2023
DOI: 10.1021/acs.joc.3c00537
|View full text |Cite
|
Sign up to set email alerts
|

Cascade Alkenylation/Intramolecular Friedel–Crafts Alkylation: High Selectivity at the C7-Position of BINOL

Abstract: An efficient and straightforward approach for the synthesis of C7 site-selective BINOL derivatives has been achieved via cost-effective Co­(III)-catalyzed C–H cascade alkenylation/intramolecular Friedel–Crafts alkylation of BINOL units and propargyl cycloalkanols. Under the advantage of the pyrazole directing group, the protocol allows the rapid synthesis of various BINOL-tethered spiro­[cyclobutane-1,1′-indenes].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…As shown in Scheme 134 (vide infra), the 6-pyrazole group of BINOL can direct the Co-catalyzed C−H activation at the less sterically hindered 7-position to form the product 390. 345 The pyrazole group of 390 was found to further direct a C−H activation at the 5-position upon Rh(III) catalysis (Scheme 129). In the presence of 5…”
Section: Rh-catalyzed Reactions At 3- 4- and 5-positionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Scheme 134 (vide infra), the 6-pyrazole group of BINOL can direct the Co-catalyzed C−H activation at the less sterically hindered 7-position to form the product 390. 345 The pyrazole group of 390 was found to further direct a C−H activation at the 5-position upon Rh(III) catalysis (Scheme 129). In the presence of 5…”
Section: Rh-catalyzed Reactions At 3- 4- and 5-positionsmentioning
confidence: 99%
“…It was found that an In 2023, Liu et al reported the use of a 6-pyrazole group to direct a C−H activation at the 7-position of BINOL by using the Co(III) catalyst 370 (Scheme 134). 345 Compound 388 was synthesized from the reaction of 6-bromoBINOL with pyrazole in the presence of Cu 2 O and K 2 CO 3 in DMSO at 130 °C over 2 d under argon. Significant racemization of BINOL was observed in this step.…”
Section: Co-catalyzed Reactions At 3-and 7-positionsmentioning
confidence: 99%